Shining New Light on Multifunctional Lanthanide Single‐Molecule Magnets. Issue 4 (15th September 2020) - Marin, Riccardo; Brunet, Gabriel; Murugesu, Muralee
Abstract: Single‐molecule magnets (SMMs) are at the forefront of new technological advances in quantum information processing and spintronics. Despite the recent impressive breakthroughs in extending the magnetic blocking temperatures beyond liquid‐nitrogen temperatures, significant challenges await in terms of integrating and addressing such compounds in devices. With this ultimate goal in mind, the design of multifunctional SMMs not only allows to imbue molecules of interest with specific properties that would allow for in situ monitoring of the SMM operation in real time, but can also provide critical insights into our understanding of the magnetic behaviour. In this Review, we highlight how magnetism and luminescence can be harmoniously combined within single molecules to achieve these objectives. The key design principles to attain the simultaneous combination of photoluminescence and slow relaxation of the magnetization are discussed, along with an outlook on how such molecules could be beneficial for emerging next‐generation spintronics devices. Abstract : The design principles in the synthesis of luminescent lanthanide single‐molecule magnets (SMMs) are the focus of this Review. Although a number of luminescent SMMs have been investigated in recent years, the majority address each component (magnetism and luminescence) in an isolated fashion. This Review highlights how their complementary nature opens the doors to some exciting applications.